Community participation and the role of school committees - Fundi, S. S (Mzumbe university, 2026)
Participation is one of the popular concepts in social development. It is a concept generally accepted in both the developed and developing countries as one of development approaches that can help speed up realization of the intended goals. Despite general acceptance, the term has been differently interpreted and practised in different parts of the world. Not only that, but also even within the same country, its interpretation has been varying among various groups. For instance, for the policy-makers participation would be considered as a vehicle for fastening development, but for the people in the implementation areas this is sometimes seen as avoidance of responsibility in the part of the government. This study aimed at exploring the notion of participation in primary education in Tanzania, with the intention of finding how people interpret and receive it. Furthermore the study focused at assessing the role of School Committees in facilitating participation. The study was completed in 2005 and it was conducted for 8 weeks in Moshi Municipality and Mvomero district. Generally the study found that the practice of participation is affected by various social, economical and political situations of the environment it is practised. Methods The researcher conducted in-depth, and one to one interviews, administered questionnaires and reviewed some official documents in order to get the data. The sample consisting of 60 community members, 10 head teachers, 10 chairpersons’ and10 members of school committees and 6 officials from the local education authorities in the study areas was used. Despite the limitations that were faced in sampling, the respondents involved in the sample were of great help and information they provided was useful in this report.